A Study on Cointegration between Indian & Brazilian Stock Markets: Examining the Relationship Between Indian and Brazilian Stock Markets (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The objective of this study is to analyze the relationship between the Indian the Brazilian Stock Markets. To find out the relationship Cointegration analysis of Indian and the Brazilian stock markets has been made over 12 years time period using Johansen test of Cointegration. The findings of the study suggested that there exists no long run causality and short run causality amongst the two stock markets. For an investor, the study has provided useful information for diversifying the investment between the two stock markets since the two markets do not have long run relationship.